2014
DOI: 10.1002/stem.1608
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cells Inhibit the NLRP3 Inflammasome by Decreasing Mitochondrial Reactive Oxygen Species

Abstract: Mesenchymal stem/stromal cells (MSCs) control excessive inflammatory responses by modulating a variety of immune cells including monocytes/macrophages. However, the mechanisms by which MSCs regulate monocytes/macrophages are unclear. Inflammasomes in macrophages are activated upon cellular "danger" signals and initiate inflammatory responses through the maturation and secretion of proinflammatory cytokines such as interleukin 1b (IL-1b). Here we demonstrate that human MSCs (hMSCs) negatively regulate NLRP3 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 46 publications
6
100
0
4
Order By: Relevance
“…Previous studies reported that STC-1 is secreted by hMSCs in response to signals from apoptotic cells and mediates an antiapoptotic action of hMSCs. 9,10 In fact, STC-1 has been shown to have multiple biological effects in mammals, involving protection of cells against ischemia, 19,20 suppression of inflammatory responses, 21,22 or reduction of reactive oxygen species [21][22][23] and the subsequent apoptosis in alveolar epithelial cancer cells, photoreceptors, or retinal ganglion cells. 10,12,13 Similarly, our data demonstrate that TNF-a-activated hMSCs secreted a large amount of STC-1, and STC-1 was responsible at least in part for the protective effects of hMSCs on corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that STC-1 is secreted by hMSCs in response to signals from apoptotic cells and mediates an antiapoptotic action of hMSCs. 9,10 In fact, STC-1 has been shown to have multiple biological effects in mammals, involving protection of cells against ischemia, 19,20 suppression of inflammatory responses, 21,22 or reduction of reactive oxygen species [21][22][23] and the subsequent apoptosis in alveolar epithelial cancer cells, photoreceptors, or retinal ganglion cells. 10,12,13 Similarly, our data demonstrate that TNF-a-activated hMSCs secreted a large amount of STC-1, and STC-1 was responsible at least in part for the protective effects of hMSCs on corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to interacting with adaptive and innate lymphocyte populations, MSCs have also been shown to modulate the differentiation, expansion, and/or function of myeloid cells towards more immunosuppressive and immunomodulatory phenotypes. These interactions include myeloid populations ranging from monocytes [28, 29], dendritic cells (DCs) [30, 31], macrophages [32, 33], and myeloid-derived suppressor cells (MDSCs) [34]. Most recently, there is also data showing modulation of granulocytes by BM and placental MSCs [35, 36].…”
Section: Clinical Status Of Msc Therapy For Immune-/inflammation-medimentioning
confidence: 99%
“…Thus, therapeutic avenues/strategies able to protect hepatocytes/biliary duct cells from insults and/ or to modulate inflammation could prevent the development of liver fibrosis/cirrhosis. It is worth noting that MSCs are immune-privileged cells able to inhibit or modulate immune responses through different and complex mechanisms, some of them causing a reduction in the amplification of proinflammatory signals [52][53][54][55], which were the subject of recent and detailed reviews [51,[56][57][58] and are briefly summarized in Fig. 2.…”
Section: Immunomodulatory Propertiesmentioning
confidence: 99%